Unchanged QRS morphology with atrial pacing in a case of WPW syndrome - Tutuianu Cristina (PACE-PACING AND CLINICAL ELECTROPHYSIOLOGY, 2019)
We present the case of a 55-year-old female who presented for a short episode of palpitation and an electrocardiogram consistent with Wolff-Parkinson-White syndrome. She underwent an electrophysiological study showing that during incremental atrial pacing and extrastimulation the stimulus to QRS and QRS morphology stayed constant while the His to ventricular (HV) interval shortened. What can be the explanation for the constant QRS morphology, despite shortening HV during atrial pacing?